Massachusetts Treasures : A Guide to Marvelous, Must-See Museums - D'Imperio, Chuck (Book collections on Project MUSE., 2018)
"Well known for its world-renowned art museums--from the Clark Art Institute in Williamstown to the Museum of Fine Arts in Boston--Massachusetts is also home to numerous institutions with more eclectic collections and, oftentimes, lower profiles. These include Mansfield's National Black Doll Museum of History and Culture, Watertown's Plumbing Museum, and Granville's Noble and Cooley Center for Historic Preservation. In Massachusetts Treasures, Chuck D'Imperio explores more than forty museums scattered throughout the Bay State, from Cape Cod to the Berkshires. Many--but not all--might be considered "offbeat," and each and every one is enchanting. Through personal visits and interviews with founders and directors, D'Imperio offers an inside glimpse into some of the Commonwealth's most unique museums, providing a valuable guide for road warriors and history buffs discovering Massachusetts either for the first or the tenth time"--